Moon camp - Gott, Barry (2021)
"Summer is here! But Jake doesn't want to go to summer camp. Even if camp is on the moon. Sure enough, he gets lost during the nature hike, his air canoe springs a leak, there's scary noises at night, and he's pretty sure he's allergic to moon dust. The worst part? He misses home. But then Sam arrives and maybe Moon Camp isn't so bad after all? Full of out-of-this-world humor, Moon Camp is a celebration of new adventures and the unexpected friends you make along the way"--
Ages 4-8
Grades K-1